Personality, belief in a just world, and attitudes toward criminal responsibility defenses: a preliminary study. Issue 1 (22nd February 2019) - Mooney, Robyn
Abstract : Purpose: In Canada, if it can be proven that a defendant was suffering from a mental disorder at the time they committed an offense, they can be found Not Criminally Responsible on Account of Mental Disorder (NCRMD). These cases are often decided by jury. The purpose of this paper is to examine the influence of the dark triad (DT), social dominance orientation (SDO) and belief in a just world (BJW) on undergraduate students' attitudes toward the NCRMD defense. Design/methodology/approach: A total of 421 undergraduate students completed questionnaires measuring SDO and the DT. After being primed for high, low or neutral BJW, they indicated their attitudes toward NCRMD. Findings: The BJW manipulation had no effect on attitudes. High-SDO/DT participants held less favorable attitudes toward NCRMD than participants who scored low on these variables, F(1, 420)=20.65, p <0.01, η p 2 = 0.05 . Psychology and criminology students had significantly more favorable attitudes toward NCRMD than business students. Practical implications: This study can be helpful in improving jury impartiality in trials involving mental illness and criminal responsibility; assessment of SDO and the DT; awareness of career roles relating to insanity defense bias; and improving the voir dire process. Originality/value: The results of this study may be used to improve the voir dire process in trials involving the issue of mental illness and criminal responsibility and to preserve the impartiality of the jurors selected for these trials.